Counteracting Radicalism with Cultural Communication in Religious Practices - Kriyantono, Rachmat (Advances in Social Sciences Research Journal, 2019)
This study aims to analyze the relationship between religious habits and radical behavior (terrorism). It is assumed that individuals who adopt cultural values ​​in practicing religious worship will not carry out terrorist activities. Religion is not only a relationship with God but also a relationship with society. This research uses content analysis method on terrorism news in online media. This research found that most terrorists are people who do not have good quality social relations with the community, tend to be closed and aloof from social relations. Terrorists also do not engage in religious activities together, including not making culture a religious instrument. This research contributes to developing the study of terrorism communication in the Indonesian context.